2009
DOI: 10.1007/s12253-009-9148-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Therapy of Cervical Intraepithelial Neoplasia for Fertility Preservation

Abstract: The aim of this study was to determine the extension of cervical intraepithelial neoplasia grade III (CIN III) into endocervical canal and depth of endocervical crypts involvement by CIN with the regard to patients' age and parity. Correlation between the area of CIN involvement and the extension into endocervical canal was estimated. A total of 218 cervical cone specimens with histologically proven CIN III were included in this study. Extension of CIN into the endocervical canal, depth of involved crypts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Heatley 9 in 280 consecutive loop specimens showed similar results and stated that almost 100% of CIN-involved crypts were within 4.8 mm of the epithelial surface. Milinovic et al 10 in 218 cone specimens also showed that the mean endocervical crypt involvement was 1.2 mm and that excision deeper than 4 mm removed >99% of CIN. In the same study, the authors also showed that in nulliparous and multiparous women, respectively, cone lengths of 15 and 18 mm did not result in any endocervical margin involvement.…”
Section: Discussionmentioning
confidence: 93%
“…Heatley 9 in 280 consecutive loop specimens showed similar results and stated that almost 100% of CIN-involved crypts were within 4.8 mm of the epithelial surface. Milinovic et al 10 in 218 cone specimens also showed that the mean endocervical crypt involvement was 1.2 mm and that excision deeper than 4 mm removed >99% of CIN. In the same study, the authors also showed that in nulliparous and multiparous women, respectively, cone lengths of 15 and 18 mm did not result in any endocervical margin involvement.…”
Section: Discussionmentioning
confidence: 93%
“…Klieamnn and colleagues found that the mean depth of the cone specimens were 17.1mm and 22.4mm in patients with positive and negative surgical margins [22]. On the other hand, Papoutsis et al [23] calculated that the optimal cone depth to achieve clear surgical margins was 10 mm, while Milinovic and colleagues [24] found that cone depth of 15mm for nulliparous and 18mm for multiparous women were sufficient to achieve a negative endocervical margin. It is important to note, however, that the last two cited studies analyzed data from younger patients and did not include patients with carcinoma in situ, micro-invasive SCC or SCC lesions on the conization specimen histology.…”
Section: Discussionmentioning
confidence: 99%
“…We found several studies which analyzed optimal cone length to avoid positive cone margin, but most of them analyzed cone depth rather than cone length [ 15 16 ]. Milinovic et al [ 17 ] reported the appropriate length of conizaiton as 18 mm in multiparous and 15 mm in nulliparous patients to secure a negative margin status, and that was the only study which analyzed appropriate cone length for CIN. In this study, we referred to the appropriate cone cut-off value in women younger than 40 years and identified the appropriate cone length as 15 mm in single quadrant disease and 20 mm in 2 or more quadrant disease with 0.1 of probability of positive cone margin.…”
Section: Discussionmentioning
confidence: 99%